Utilizing Hilbert–Huang transform in detection some of mechanical properties of the refractory metals. (February 2016) - Mohammed, Arshed Abdulhamed; Haris, Sallehuddin Mohamed; Nuawi, Mohd Zaki
Abstract: This study is one of the first to report on the use of Hilbert–Huang transform (HHT) to determine the modulus of elasticity of a material, which is one of the most important properties of metals. In addition, this study involves an analytical study of the process of transfer of energy, which was represented in the form of intrinsic mode functions (IMFs). Moreover, the distribution of IMFs within the time-frequency-plain was determined by testing eight test specimens. Five test specimens were refractory materials, namely, Ti, Ti6AL4V, Zr, Nb, and Ta, and the other three were non-refractory materials, namely, Al, Brass, and ST4340. The new setup was composed of Mg and involves the use of two piezoelectric transducers, which were used as the emitter and receiver. The setup was designed and implemented in this research based on Mg usage to test the metals. First, a new relationship was derived between the pressure transmission coefficient (PTC) of the transmitted wave (through the emitter-water-test specimen-Mg to the receiver) and the corresponding values of the product of the density ( ρ ) and the modulus of elasticity ( E ) for the same test specimen. Another relationship was established between the PTCs and the total energy transmitted at high frequencies. This energy indicates the summation of IMFs that have high frequencies (THIMFs), higher than 10 kHz, can determine E better than TOF for most test specimens. To verify this results, with regard to the second conclusion, a new simulation for this setup was carried out using Simulink in MATLAB. Twelve theoretical tests were done, for high acoustic impedance metals, like Hf, Mo, WNiFe and W in addition to test the same group which was tested experimentally. The results of theoretical tests supported the experimental results except for Nb. Most of the conclusions were obtained through practical results and analytical studies. The results proved that THIMFs can determine the change in the microstructure of the alloys when the ratio of their constituent elements was changed. Highlights: The modulus of elasticity ( E ) of the test specimens (TSs) were calculated using HHT. The PTCs of the wave have a regular relationship with Eρ . Relation of PTCs with high ∑ I M F s frequencies is a 5th-degree polynomial equation. From 180 to 360 kHz, the marginal spectrum can detect changes in TS microstructure. Energy transmission levels were identified within five frequency ranges.